Contextualization of Hadith in Contemporary Education - Sayfuddin; Ahmad Muhammad Tidjani (Penerbit Hellow Pustaka, 2025)
This study examines the contextualization of hadith in contemporary education, focusing on the values ​​of lifelong learning contained in the hadith of the Prophet Muhammad. Contextualization is carried out through understanding the textual and historical meaning of hadith and its relevance to modern educational problems such as moral crisis, gender equality, and technological development. The purpose of this study is to explain how educational hadith can be actualized in contemporary learning, specifically through the Contextual Teaching and Learning (CTL) model. The research method uses a qualitative approach through literature review with content analysis. The results show that hadiths, such as the obligation to seek knowledge and the encouragement of lifelong learning, provide a philosophical basis for modern education. With a contextual approach, hadith values ​​can be effectively integrated into modern learning systems through CTL, character education, and social projects based on hadith values. This study confirms that hadith have high elasticity and relevance in addressing the challenges of contemporary education.